Retracted:-Identification of Benzoxazolinone Derivatives Based Inhibitors for Depression and Pain Related Disorders Using Human Serotonin and Norepinephrine Transporter as Dual Therapeutic Target: A Computational Approach - Selvaraj Manikandan,; AR Saranya,; Thirugnanasambandam Ramanathan,; Krishnan Selvarajan Kesavanarayanan,; LK Teh,; MZ Salleh, (International Journal of Phytomedicine, 2015)
Retracted:-Identification of Benzoxazolinone Derivatives Based Inhibitors for Depression and Pain Related Disorders Using Human Serotonin and Norepinephrine Transporter as Dual Therapeutic Target: A Computational Approach